Adherence to Coronavirus Disease 2019 Preventive Measures in a Representative Sample of the Population of the Canton of Vaud, Switzerland - Audrey Butty; Nolwenn Bühler; Nolwenn Bühler; Jérôme Pasquier; Julien Dupraz; Vincent Faivre; Sandrine Estoppey; Cloé Rawlinson; Semira Gonseth Nusslé; Murielle Bochud; Valérie D’Acremont; Valérie D’Acremont (International Journal of Public Health, 2022)
Objectives: We quantified adherence to COVID-19 preventive measures and explored associated factors, after the first and during the second Swiss epidemic waves.Methods: With an observational cohort study in a representative sample of individuals aged 15 years and more, we analysed the association between self-reported adherence to COVID-19 preventive measures (respect of simple hygiene rules; respect of social distancing rules; wearing a mask) and socio-demographic factors, the existence of a chronic disease, and the existence of a previous confirmed COVID-19 episode.Results: Highest adherence was to simple hygiene rules, followed by social distancing rules and mask wearing, with a slight decrease for simple hygiene rules and a strong increase for mask wearing between visits. Men were significantly less likely to respect simple hygiene rules and wear a mask in public. Participants aged 65 years and more (versus 25–64 years) and those with at least one chronic disease (versus none) were two times more likely to respect social distancing rules and wear a mask.Conclusion: Adherence to social distancing rules and mask wearing was rather poor, especially compared to other countries.